SENGKETA PULAU BERHALA - Arif Rahim (Universitas Batanghari Jambi, 2014)
This paper discusses the ongoing dispute between the Berhala island 1983 to 2013 Through the history of the processual approach, it can be explained that the existence of a group of Berhala islands has significance for two provincial conflict in ownership, ie, between the Jambi Province and Riau Province. Furthermore, since 2003 after Riau province was divided, between the Jambi Province of Riau Islands province. Both parties to the dispute have the same claim and the reason for the strong evidence that serve as the basis of the demands. Reasons and evidence are classified into several aspects: historical, and socio-cultural, as well as administrative and juridical aspects. Mediation both sides done in several ways. Firstly, direct talks between the two warring regions, the latter through the decision of the Minister of Home Affair, and the third, through the decision of the Supreme Court, and last through the decision of the Constitutional Court. After a failed attempt to reach agreement through direct negotiations, settlement of disputes resolved through 44 Regulation of the Minister of Home Affir in 2011, which set a group of Berhala Island into the East Tanjung Jabung district, Jambi Province. Riau Islands are not satisfied with the Regulation of the Minister make a claim to the Supreme Court (MA). The lawsuit is accepted by the Supreme Court, as well as cancel Permendagri 44. Jambi party who is not satisfied with the subsequent Supreme Court decision to take legal actions with mangajukan claim to the Constitutional Court (MK). The Court then rejected the appeal and issue a decision Jambi strengthen the Supreme Court decision and decided to enter Berhala Great Barrier Island in Lingga regency, Riau Islands Province. With the release of the Court's decision, it ended Berhala island dispute has been going on for about 30 years.